The Domination Of Indonesian Ulama Council Withhold Law Of Halal Product Guarantee - Muchamad Ali Safa'at (Arena Hukum, 2022)
In the relation of law and politic perspective, law is not a neutral entity. Law is a battleground domain for political interests and as instrument of group domination. It can be seen in the formation and implementation of the Halal Law. This research aims to analyze the role of Indonesian Ulama Council (MUI) in the formation and implementation of the Halal Product Guarantee Act. This research uses socio legal method. The research result shows that MUI dominates by hold up the formation and implementation of the Halal Law. This is done by dominating the legitimacy of identity as a religious organization and using a network of organizations and political actors so that the process of establishing rules and administering halal law by BPJPH is hampered. Delegitimacy and disturbance are also experienced through requests for judicial review of the Halal Certification Law to the Constitutional Court and lawsuits to the courts.